Abandoned Bodies, Lost Gods: A Bioenergy Economy-based Trauma - Farzad Goli (International Journal of Body, Mind and Culture, 2023)
The Bioenergy Economy (BEE) is a contextual and evidence-based model of care that is focused on the development of bodily awareness.  In the course of BEE-based trauma therapy, by changing the contexts of embodied sensation, narrative, relationship, and intentionality, the fixed meaning-making systems (pre-linguistic and linguistic) around the trauma were gradually deconstructed. In this essay, we follow the story of a young woman in the course of BEE-based trauma therapy. She had come in for her existential and religious crisis but was guided to recovery from the post-traumatic stress of a domestic assault.